2022
DOI: 10.1186/s12917-022-03140-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free culture supernatants of Lactobacillus spp. and Pediococcus spp. inhibit growth of pathogenic Escherichia coli isolated from pigs in Thailand

Abstract: Background Pathogenic Escherichia coli (E. coli) is an important causative agent for infectious diseases in pigs and causes significant economic loss. The global concern of antimicrobial resistance of bacteria raises awareness of the alternative ways of using antimicrobial peptides (AMPs). The study was aimed to identify and test the efficacy of AMPs from Lactobacillus spp. against the growth of pathogenic E. coli isolated from pigs in Thailand. Briefly, cell-free culture supernatants (CFCS) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…The antimicrobial activity of CFSs were tested in accordance with the Kaewchomphunuch et al protocol [44]. As a negative control, 50 µL of MRS, adjusted to pH 3.8 with hydrochloric acid 1N (Sigma-Aldrich), was used.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The antimicrobial activity of CFSs were tested in accordance with the Kaewchomphunuch et al protocol [44]. As a negative control, 50 µL of MRS, adjusted to pH 3.8 with hydrochloric acid 1N (Sigma-Aldrich), was used.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…As a negative control, 50 µL of MRS, adjusted to pH 3.8 with hydrochloric acid 1N (Sigma-Aldrich), was used. Antibacterial activity has been evaluated after 72 h, at 15 • C and 30 • C, measuring the diameter (mm) of the clear zone of inhibition (ZOI) around the inoculated wells [44]. The tests were conducted in triplicate.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Organic acids, bacteriocins and hydrogen peroxide are the antimicrobial metabolites produced by probiotics (Ispirli et al, 2015). The cell free culture supernatant (CFCS) of L. acidophilus and P. pentosaceus found to inhibit the growth of E. coli strains, that may be due to the fact that several active constituents function together in CFCS (Kaewchomphunuch et al, 2022). Furthermore, the CFCS in our investigation requires additional research to identify active compounds in order to substantiate the inhibitory activity shown against the Vibrio spp.…”
Section: Antibacterial Activitymentioning
confidence: 94%
“…Hydrophobicity of the isolates was performed by growing the isolates in MRS broth at 30C for 24 hours, centrifuged for 15 minutes at 3000 G. The resultant pellet was used for measurement cell-surface hydrophobicity (Liu et al, 2020). Cross streaking assay was done by streaking single colony of the isolates ON495586, ON491817, ON479264, ON478992, ON478991 and ON564885, incubating them anaerobically at 30C for 24 h on the MRS agar plates and examining for inhibition zone near the contact point of the streaking lines (Kaewchomphunuch et al, 2022). The statistical analysis was performed with SPSS Version 17.0 using one way ANOVA and mean comparison employing Duncan's multiple range test.…”
Section: Methodsmentioning
confidence: 99%